2023
DOI: 10.1039/d2tc04842f
|View full text |Cite
|
Sign up to set email alerts
|

The importance of a good solvent of conjugated polymers for preparing dopant solution on the electrical and mechanical properties of sequentially doped conjugated polymer films

Abstract: In this work, we sequentially doped poly(3-hexylthiophene) (P3HT) films with 2,3,5,6-tetrafluoro-7,7,8,8-tetracyanoquinodimethane (F4TCNQ) from multiple good solvent/orthogonal solvent blends with different ratios. Combining UV-visible (UV-vis) spectroscopy, grazing-incidence wide-angle X-ray diffraction (GIXRD),...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 34 publications
1
4
0
Order By: Relevance
“…The very high roughness of sample 2 films (in Figure S5), as compared to samples 1 and 3, is a strong reminder that also the AFM roughness criterium needs to be handled with care and plausibly applies only to closely similar morphologies. Figure c shows that the in-plane 020 reflection peak of doped form I′ (sample 1) and form I (sample 3) shifts to higher q because F4TCNQ occupies the lamellar region of the crystallites, in accordance with doped P3HT films reported previously. , The in-plane 020 reflection peak position of form II (sample 2) has nearly no change before and after F4TCNQ doping, further verifying that form II of P3BT is difficult to dope with F4TCNQ.…”
Section: Resultssupporting
confidence: 85%
See 3 more Smart Citations
“…The very high roughness of sample 2 films (in Figure S5), as compared to samples 1 and 3, is a strong reminder that also the AFM roughness criterium needs to be handled with care and plausibly applies only to closely similar morphologies. Figure c shows that the in-plane 020 reflection peak of doped form I′ (sample 1) and form I (sample 3) shifts to higher q because F4TCNQ occupies the lamellar region of the crystallites, in accordance with doped P3HT films reported previously. , The in-plane 020 reflection peak position of form II (sample 2) has nearly no change before and after F4TCNQ doping, further verifying that form II of P3BT is difficult to dope with F4TCNQ.…”
Section: Resultssupporting
confidence: 85%
“…Figure 2c shows that the in-plane 020 reflection peak of doped form I′ (sample 1) and form I (sample 3) shifts to higher q because F4TCNQ occupies the lamellar region of the crystallites, in accordance with doped P3HT films reported previously. 45,56 The in-plane 020 reflection peak position of form II (sample 2) has nearly no change before and after F4TCNQ doping, further verifying that form II of P3BT is difficult to dope with F4TCNQ. FTIR spectroscopy is sensitive to the electronic states of F4TCNQ within the doped P3BT samples.…”
Section: ■ Results and Discussionmentioning
confidence: 83%
See 2 more Smart Citations
“…In that strategy, the dopant is brought into contact with the P3HT film after casting the latter onto a solid substrate . For example, the introduction of the dopant has been made by dipping the film into a dopant solution, through spin-coating or drop-casting of a dopant solution onto the film but also by evaporation. ,, Several authors reported that sequential doping does not affect the crystallinity and morphology of P3HT films. ,,,, They also evidenced a direct correlation between the values of the electronic conductivity measured after doping with F 4 TCNQ vapors and the crystallinity degree of the pristine P3HT film, varied through the solvent used for spin-coating regioregular P3HT or the fraction of regioregular and regiorandom P3HT. , At the same doping level, Jacobs et al . also evidenced that dipping into the F 4 TCNQ solution of spin-coated P3HT films resulted in enhanced conductivities approaching 10 S/cm, i.e., an order of magnitude greater than those measured for the films prepared by spin-coating P3HT:F 4 TCNQ blend .…”
Section: Introductionmentioning
confidence: 99%